2006
DOI: 10.1002/ps.1320
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathy in crop/weed interactions — an update

Abstract: Since varietal differences in allelopathy of crops against weeds were discovered in the 1970s, much research has documented the potential that allelopathic crops offer for integrated weed management with substantially reduced herbicide rates. Research groups worldwide have identified several crop species possessing potent allelopathic interference mediated by root exudation of allelochemicals. Rice, wheat, barley and sorghum have attracted most attention. Past research focused on germplasm screening for elite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
277
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(294 citation statements)
references
References 113 publications
(197 reference statements)
3
277
0
2
Order By: Relevance
“…Of particular interest have been potentially allelopathic compounds that may inhibit growth of weeds (Belz 2007), but also have been implicated in allelopathic interactions with crop plants (Roth et al 1999;Wu et al 2007). Besides effects on plants, allelochemicals may be involved in modifications of physical properties of soil or activities of soil microorganisms (Bertin et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest have been potentially allelopathic compounds that may inhibit growth of weeds (Belz 2007), but also have been implicated in allelopathic interactions with crop plants (Roth et al 1999;Wu et al 2007). Besides effects on plants, allelochemicals may be involved in modifications of physical properties of soil or activities of soil microorganisms (Bertin et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat root exudates that may have allelopathic potential are phenolic compounds (Wu et al 2001). The major group of root exudates from sorghum with allelopathic properties is the benzoquinonones called sorgoleone {2-hydroxy-5-methoxy-e- [(8Z,11Z-8,11,14-pentadecatriene]-p-benzoquinone} (Chang et al 1986;Belz 2007). Production of allelopathic phenolics by wheat seedling roots grown on agar medium have been shown to vary by types and levels, depending upon the cultivar (Wu et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of control against some weeds might not occur immediately, as does that of commercial herbicides, but could build over time, as with most natural products (Belz 2007). Netzley et al (1988) reported that the concentration of sorgoleone exuded into the soil from S. bicolor roots can reach 10-100 μM.…”
Section: Resultsmentioning
confidence: 99%
“…Such chemicals therefore constitute an important mediator of population dynamics because they determine the pattern and density of vegetation, in natural and crop systems alike. Numerous plants have been reported to be allelopathic, including lichens, alfalfa, cucumber, rye, barley, wheat, rice, soybeans, and sorghum (Singh et al 2003;Belz 2007;Albuquerque et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…2 This particular class of allelochemicals derives from the cyclic hydroxamic acids DIBOA (4-dihydroxy-2H-1,4-benzoxazin-3(4H)-one) and DIMBOA (2,4-dihydroxy-7-methoxy-2H-1,4-benzoxazin-3(4H)-one), which are contained in root exudates from many grasses, among them several major crops such as wheat, rice and maize. 3,4 We were able to show that APO and AMPO have the potential to bind to histone deacetylases (HDACs), 2 an evolutionarily highly conserved class of enzymes that govern the accessibility of the DNA by removal of acetyl groups from various amino acid residues of histone proteins. Histone acetylation is a dynamic epigenetic mark that correlates with relaxed chromatin conformation, accessible DNA and transcriptional activity (Fig.…”
mentioning
confidence: 99%